Pemberdayaan Pesantren: Membangun Generasi Islami melalui Pembinaan Keterampilan Berbahasa Asing - Hari Prastyo (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2017)
Pesantren is a religious educational institution managed by the society that is called as Pengasuh. Therefore, Pengasuh is a leader in a community. The educational background of Pengasuh effects activities developed in it. Furthermore, the activities in pesantren relate to the students’ competence and skills. In the modern and global world, the students’ competence and skills should be the primary consideration in developing program at Pesantren. One of the competencies and skills that must be mastered by the students are foreign-language skills. This article discussed about Pesantren Empowerment through the Development of Foreign Language Skills Program to Create an Islamic Generation. This was a research article that used Research and Development Design. This research was conducted at Pesantren I'anatut Tholibin Mojokerto. The first step of this research was to do Need Analysis by using questionaire and interview. Based on the results of questionaire and interview, the researchers developed a program to empower pesantren. The results of this research will be useful for pengasuh, because the result of this research will give a real contribution for pesantren in the form of program that is related to the competence and skills of students as a form of empowerment for pesantren